ICT and the Education of Refugees : A Stocktaking of Innovative Approaches in the MENA Region - Lewis, Kent; Thacker, Simon (World Bank, Washington, DC, 2017)
More than 10 million school-age children have been forced out of school in the Middle East and North Africa (MENA) due to armed conflict in Syria, Iraq, Yemen, Libya and other countries. Most are displaced internally but others have fled across borders to seek refuge. As governments and international agencies struggle to ensure these children a safe learning environment and a good quality education, many look to information and communications technology (ICT) to provide at least part of the solution. The use of smartphones and other mobile devices, ubiquitous even among impoverished refugees, can provide a platform that educators can leverage to reach marginalized children and youth. This paper aims to inform discussion on the role information and communications technology (ICT) can play in the educational response to the refugee crisis in the MENA. It provides a clear and concise snapshot of the role ICT has played, the promise it holds, the projects that are currently under preparation and what more might be done. The purpose of this note is to provide a clear and concise snapshot of the role ICT has played, the promise it holds, the projects that are currently under preparation, and what more might be done. This is in no way a comprehensive assessment but rather an attempt to promote dialogue and inform programs.